EFEKTIVITAS MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION BERBANTUAN MEDIA TRIQUMATH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Lilik Puspita, Leila; Sumaji; Suryo Bintoro, Henry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical problem-solving ability is one of the essential competencies in mathematics learning because it helps students understand, analyze, and solve various problems systematically. However, the mathematical problem-solving ability of most students is still relatively low, causing difficulties in solving mathematical problems. This study aimed to analyze the effectiveness of the Realistic Mathematics Education (RME) learning model assisted by TriquMath media on students’ mathematical problem-solving ability. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent pretest-posttest control group design. The population consisted of all seventh-grade students of SMP Negeri 1 Mejobo, totaling 317 students. The sample comprised 64 students, including 32 students from class VII B as the experimental group and 32 students from class VII E as the control group. Data were collected through tests, interviews, and documentation. The results showed that there was a significant difference in students’ mathematical problem-solving ability before and after the implementation of the RME learning model assisted by TriquMath media. The N-Gain score of 0.60 indicated a moderate level of improvement. Furthermore, the average posttest score of the experimental group was 86.30, which was higher than that of the control group at 38.48. The RME learning model assisted by TriquMath media was effective in improving students’ mathematical problem-solving ability. The implication of this study is that the RME learning model assisted by TriquMath media can serve as an alternative approach for mathematics teachers in designing more contextual, interactive, and effective learning activities to enhance students’ mathematical problem-solving ability.